The Impact of Environmental Uncertainty and Accounting Information Systems on Managerial Performance of Micro, Small, and Medium Enterprises in Parepare City - Fatimah; Sariana Damis; Hernianti Harun; Yadi Arodhiskara; Nurwani; Raoda (www.amertainstitute.com, 2025)
This study investigates how accounting information systems and environmental uncertainty affect the managerial performance of UMKM in Parepare. Multiple linear regression techniques are used in this quantitative study. Purposive sampling was used to choose the 86 UMKM managers registered in the Rumah BUMN Parepare program as responders. Questionnaires were used to gather data, and SPSS was used for analysis to assess the model’s validity, reliability, and significance. According to the study’s findings, accounting information systems significantly and favorably affect management performance (p < 0.001), but environmental uncertainty has no discernible effect (p = 0.918). Other factors outside the model also have a considerable impact, as indicated by the coefficient of determination (R2) of 16.9%. This study advances the body of literature on managerial performance by emphasizing the significance of accounting information systems and the limited role of environmental uncertainty. UMKM managers and policymakers can learn from these findings how important it is to create integrated and structured accounting information systems to facilitate decision-making and operational efficiency. The findings may not accurately represent the circumstances of UMKM in other areas or industries because this study is restricted to UMKM in the city of Parepare. The empirical investigation of the variables influencing managerial performance in UMKM is the main topic of this quantitative study.